1/3+1/4+1/5+42/45
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(-\dfrac{4}{7}-\dfrac{5}{13}\cdot\dfrac{-39}{25}+\dfrac{-1}{42}:\dfrac{-5}{6}\)
\(=\dfrac{-4}{7}+\dfrac{3}{5}+\dfrac{1}{35}\)
\(=\dfrac{-20}{35}+\dfrac{21}{35}+\dfrac{1}{35}\)
\(=\dfrac{2}{35}\)
\(a.\dfrac{-4}{7}-\dfrac{5}{13}\times\dfrac{-39}{25}+\dfrac{-1}{42}:\dfrac{-5}{6}\)
\(=\dfrac{-4}{7}+\dfrac{3}{5}+\dfrac{1}{35}\) \(=\dfrac{1}{35}+\dfrac{1}{35}=\dfrac{2}{35}\)
\(b.\dfrac{2}{9}\times\left[\dfrac{4}{5}:\left(\dfrac{1}{5}-\dfrac{2}{15}\right)+1\dfrac{2}{3}\right]-\dfrac{-5}{27}\)
\(=\dfrac{2}{9}\times\left[\dfrac{4}{5}:\dfrac{1}{15}+\dfrac{5}{3}\right]-\dfrac{-5}{27}\)
\(=\dfrac{2}{9}\times\left(12+\dfrac{5}{3}\right)-\dfrac{-5}{27}\)
\(=\dfrac{2}{9}\times\dfrac{41}{3}-\dfrac{-5}{27}=\dfrac{82}{27}-\dfrac{-5}{27}=\dfrac{29}{9}\)
Bạn tự trình bày nha!
a, x = (21/4 - 39/4): 15/4
b, x = (23/5+ 1/9) : 42/8
c, Đổi 75%= 3/4 ; 45%= 9/20
x = (3/4 + 2/3): 1/2 -1
d, x = (5/6+ 3/4) : 1/2-1
a) Ta có: \(\dfrac{-5}{18}+\dfrac{32}{45}-\dfrac{9}{10}\)
\(=\dfrac{-25}{90}+\dfrac{64}{90}-\dfrac{81}{90}\)
\(=\dfrac{-42}{90}=-\dfrac{7}{15}\)
b) Ta có: \(\left(-\dfrac{1}{4}+\dfrac{51}{33}-\dfrac{5}{3}\right)-\left(-\dfrac{15}{12}+\dfrac{6}{11}-\dfrac{42}{29}\right)\)
\(=\dfrac{-1}{4}+\dfrac{17}{11}-\dfrac{5}{3}+\dfrac{5}{4}-\dfrac{6}{11}+\dfrac{42}{29}\)
\(=\dfrac{-5}{3}+\dfrac{42}{29}\)
\(=\dfrac{-145}{87}+\dfrac{126}{87}=\dfrac{-19}{87}\)
c) Ta có: \(1-\dfrac{1}{2}+2-\dfrac{2}{3}+3-\dfrac{3}{4}+4-\dfrac{1}{4}-3-\dfrac{1}{3}-2-\dfrac{1}{2}-1\)
\(=\left(1-1\right)-\left(\dfrac{1}{2}+\dfrac{1}{2}\right)+\left(2-2\right)-\left(\dfrac{2}{3}+\dfrac{1}{3}\right)+\left(3-3\right)-\left(\dfrac{3}{4}+\dfrac{1}{4}\right)+4\)
\(=-1-1-1+4\)
=1
a) Ta có: −518+3245−910−518+3245−910
=−2590+6490−8190=−2590+6490−8190
=−4290=−715=−4290=−715
b) Ta có: (−14+5133−53)−(−1512+611−4229)(−14+5133−53)−(−1512+611−4229)
=−14+1711−53+54−611+4229=−14+1711−53+54−611+4229
=−53+4229=−53+4229
=−14587+12687=−1987=−14587+12687=−1987
c) Ta có: 1−12+2−23+3−34+4−14−3−13−2−12−11−12+2−23+3−34+4−14−3−13−2−12−1
=(1−1)−(12+12)+(2−2)−(23+13)+(3−3)−(34+14)+4=(1−1)−(12+12)+(2−2)−(23+13)+(3−3)−(34+14)+4
=−1−1−1+4=−1−1−1+4
=1
Bài 2:
a: =>x-35=-23
=>x=12
b: =>|x-8|=13
=>x-8=13 hoặc x-8=-13
=>x=21 hoặc x=-5
Bài 1:
a: =42-98-42+12-12=-98
b: =10x4x3x(-25)=40x(-25)x3=-1000x3=-3000
câu 1)
\(\dfrac{-12}{18}+\left(\dfrac{-21}{35}\right)=\dfrac{-19}{15}\)
câu 2)
\(-\dfrac{3}{21}+\dfrac{6}{42}=0\)
câu 3)
\(-\dfrac{18}{24}+\dfrac{15}{21}=-\dfrac{1}{28}\)
câu 4)
\(\dfrac{1}{6}+\dfrac{2}{5}=\dfrac{17}{30}\)
câu 5)
\(\dfrac{3}{5}+\left(-\dfrac{7}{4}\right)=-\dfrac{23}{20}\)
câu 6)
\(\left(-2\right)+\left(\dfrac{-5}{8}\right)=\dfrac{-21}{8}\)
câu 7)
\(\dfrac{1}{-8}+\left(-\dfrac{5}{9}\right)=-\dfrac{49}{72}\)
câu 8)
\(\dfrac{4}{13}+\dfrac{12}{39}=\dfrac{8}{13}\)
câu 9)
\(\dfrac{1}{21}+\dfrac{1}{28}=\dfrac{1}{12}\)
câu 10)
\(-\dfrac{3}{29}+\dfrac{16}{58}=\dfrac{5}{29}\)
câu 11)
\(\dfrac{8}{40}+\left(-\dfrac{36}{45}\right)=-\dfrac{3}{5}\)
câu 12)
\(-\dfrac{8}{18}+\left(-\dfrac{15}{27}\right)=-1\)
câu 13)
\(\dfrac{13}{30}+\left(-\dfrac{1}{5}\right)=\dfrac{7}{30}\)
câu 14)
\(\dfrac{2}{21}+\dfrac{1}{28}=\dfrac{11}{84}\)
câu 15)
\(5+\left(-\dfrac{3}{4}\right)=\dfrac{17}{4}\)
câu 16)
\(\dfrac{18}{24}+\dfrac{45}{-10}=-\dfrac{15}{4}\)
1; - (-66) + 34 + (-73) - 27 + 99
= 66 + 34 - 73 - 27 + 99
= (66 + 34) - (73 + 27) + 99
= 100 - 100 + 99
= 0 + 99
= 99
2; 54 - (45 - 30 + 54) - 30 + 5
= 54 - 45 + 30 - 54 - 30 + 5
= (54 - 54) + (30 - 30) - (45 - 5)
= 0 + 0 - 40
= - 40
103\60
1.71666666667